The influence of lay-up design on the performance of bi-stable piezoelectric energy harvester. (1st February 2017) - Pan, Diankun; Li, Yanqi; Dai, Fuhong
Abstract: Bi-stable composite laminates with piezoelectric transducers have been shown to capture energy over a wide frequency range and deliver significantly greater energy than resonant devices. In this work, the influence of lay-up design on the performance of bi-stable piezoelectric energy harvester (BPEH) based on bi-stable hybrid symmetric laminate (BHSL) is analyzed and verified. The initial voltage induced by stable configuration and longitudinal curvature of BPEH with different lay-up and hybrid width were calculated and analyzed by a static finite element analysis. The lay-up can vary initial voltage and longitudinal in opposite directions, and hybrid width can adjust these two variables in the same direction. The strain variations of piezoelectric transducer between two stable configurations were also analyzed. The initial voltage of BPEH depends on strain variations in the two directions. And then the finite element results are verified by experiment. Three types of BPEH were manufactured and actuated by two methods to measure their output powers. These BPEHs presented different dynamic responses, and the output powers under different vibration modes were measured. The highest output power of BPEH in this work is 42.2 mW and the highest power density is 78.1 mW/cm 3 .